Implementasi Pijat Oksitosin Terhadap Kelancaran ASI pada Pasien Post Partum Sectio Caesarea di RS Jakarta Barat - Kurnaen Kurnaen; Rizki Bahtiyar; Edi Santoso (Lembaga Pengembangan Kinerja Dosen, 2026)
Breast milk production can be accelerated with non-pharmacological measures, such as oxytocin massage. Oxytocin massage is considered more effective in increasing breast milk production because it stimulates the release of the hormone oxytocin, which is influenced by the thoughts and feelings of postpartum mothers. The purpose of this case report is to determine the effects of oxytocin massage on breast milk production in postpartum mothers at a West Jakarta Hospital. Methods: This study used a qualitative approach with a descriptive design, focusing on case studies. Data were collected through interviews and observations of postpartum mothers. Results indicate that oxytocin massage provides a sense of comfort and relaxation, contributing to increased breast milk production in postpartum mothers. The average increase in breast milk production after oxytocin massage ranged from 8 to 18 ml/cc. Conclusion: Applying oxytocin massage to postpartum mothers for three consecutive days, three times daily, for fifteen minutes each session, has been shown to increase breast milk production in patients.